2021
DOI: 10.3390/brainsci11111428
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Dopamine Transporter Availability Is Not Associated with Food Craving in Lean and Obese Humans; a Molecular Imaging Study

Abstract: Brain dopamine signaling is essential for the motivation to eat, and obesity is associated with altered dopaminergic signaling and increased food craving. We used molecular neuroimaging to explore whether striatal dopamine transporter (DAT) availability is associated with craving as measured with the General Food Craving Questionnaire-Trait (G-FCQ-T). We here show that humans with obesity (n = 34) experienced significantly more craving for food compared with lean subjects (n = 32), but food craving did not cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
(87 reference statements)
0
2
1
Order By: Relevance
“…Another study with rodent models of DIO 53 showed decreased striatal DD2R availability and greater extracellular dopamine in obesity-prone (OP) compared with obesity-resistant (OR) rats 53 . While this study also showed lower expression of the presynaptic dopamine transporter (DAT) in OPs 53 , there seems to be no reliable association between DAT availability and obesity in clinical studies 54 56 .…”
Section: Discussioncontrasting
confidence: 73%
“…Another study with rodent models of DIO 53 showed decreased striatal DD2R availability and greater extracellular dopamine in obesity-prone (OP) compared with obesity-resistant (OR) rats 53 . While this study also showed lower expression of the presynaptic dopamine transporter (DAT) in OPs 53 , there seems to be no reliable association between DAT availability and obesity in clinical studies 54 56 .…”
Section: Discussioncontrasting
confidence: 73%
“…In contrast, Versteeg et al 134 found no effect of meal timing on insulin sensitivity. On the other hand, significant meal time‐dependent changes were found in the brain dopamine and serotonin system 135 …”
Section: Circadian Desynchrony Disturbs Glucose Metabolismmentioning
confidence: 99%
“…Although the exact underlying mechanisms of the alterations in appetite and eating behaviour in obesity remain unclear, increasing evidence points towards alterations in the signaling pathways mediating food reward (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%